A clinical study of displaced clavicle fractures treated with precontoured locking compression plate - Naidu, E. Dilip Kumar; Anand, A. V. (International Journal of Research in Orthopaedics, 2017)
Background: Fractures which involve the clavicle are very common and account for almost 5-10% of all the fractures and up to around 45% of those which involve the shoulder girdle. Most of these fractures occur due to a direct blow to the anterior chest wall or by falling on the outstretched hand. Traditionally, clavicular fractures have been treated with conservative methods, but the outcome was poor, leading to patient dissatisfaction. An option is the precontoured locking plates which provide immediate relief, stabilization and early mobilization, more so because they do not require further bending. Methods: 50 patients, above 18 years of age, with closed displaced clavicular fractures were included in the study. Clinical evaluation was done for all the patients using the Constant-Murley score. Precontoured locking compression plate was inserted surgically for the treatment of the fracture and follow-up was done for 6 months postoperatively. Results: Out of the 50 patients studied, 42 were males (84%) and 8 (16%) were females. Most of the patients belonged to 21-50 years of the age group. Road traffic accidents were the most common cause (98%) for this type of fractures. Most of the fractures were united by 11-12 weeks of duration (42%), closely followed by a time period of 9-10 weeks (40%). Most of the patients showed full range of movement (84%), while 6% showed movements which were restricted by 200 and 10% showed 300 restrictions. In 32% of the cases, the outcome was excellent while only 6% of the patients showed a fair outcome. Conclusions: Displaced mid-shaft clavicle fractures treated with precontoured locking compression plates gave good functional outcome and patient satisfaction with excellent reunion rates.